High heat flux thermal solution of high power system - Png, Wee Kiet (2015)
Advancement in high power technology has spurred researchers to look for more high power thermal solutions. The main heat transfer cooling methods are pool boiling, flow boiling and spray cooling. Of these high heat flux cooling techniques, spray cooling shows the most potential for high heat flux thermal solution with reported heat flux of up to 1200 W/cm2 and also higher recognition among researchers in recent years. In this present study, open loop spray cooling was used to study the effect of enhanced surfaces (extended fins, coatings and rough surface) on the performance of spray cooling heat flux. The extended fins, coatings and rough surface were machined / coated onto a copper block with a heating surface of 20 mm diameter. Using water as the cooling medium for spray cooling, the heat fluxes of four different fin configurations (0.35 pin fins, 0.35 straight fins, 0.5 pin fins and 0.5 straight fins), rough surface, and h-BN (Hexagonal Boron Nitride) and NCG (Nanocrystalline Graphite) coatings were calculated and tabulated in this study. The 0.35 pin fins exhibited the best heat flux improvement of 29% over the bare surface. The study shows that fins spacing and fins width affect heat flux performance more than the total wetted surface area of the fins. The study also shows that vertically aligned NCG is a potential material for heat transfer enhancement coating with a heat flux enhancement of 28% at the centre of the heated surface. Besides using water, 1500 ppm butanol in DI water was also used as cooling medium to investigate the effect of cooling fluid properties on spray cooling in this study. Three surfaces (0.35 pin and straight fins and bare surface) were tested with the 1500 ppm butanol mixture. The bare surface showed the highest heat flux improvement of 12.5% over using water.